2008
DOI: 10.1002/pssb.200743500
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐wave spectra and magnetization of ferro–ferrimagnetic double layers

Abstract: The spin‐wave spectra and magnetization of the ferro–ferrimagnetic double layers are studied by using a linear spin‐wave approximation and retarded Green's‐function method. We obtain the four branches of the spin‐wave spectra. Two energy gaps are found to exist in the energy band. The effects of the interlayer exchange coupling, the intralayer exchange coupling and the spin quantum numbers on the spin‐wave spectra and the energy gaps are discussed. The minimum (maximum) value point on the spin‐wave spectra and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Jiang et al theoretically predicted the existence of multiple possible spin waves in such bilayer films. [12] Monteiro et al [13] have also theoretically shown, by simulations, that an inhomogeneous internal magnetic field, caused by the exchange field between hard and soft magnetic layers, does exist in exchange-coupling region within an FePt/Fe bilayer system. They also predicted that rich spin-wave modes related to the variation of the local effective magnetic field across Fe layer exist in the exchange-coupling films.…”
mentioning
confidence: 96%
“…Jiang et al theoretically predicted the existence of multiple possible spin waves in such bilayer films. [12] Monteiro et al [13] have also theoretically shown, by simulations, that an inhomogeneous internal magnetic field, caused by the exchange field between hard and soft magnetic layers, does exist in exchange-coupling region within an FePt/Fe bilayer system. They also predicted that rich spin-wave modes related to the variation of the local effective magnetic field across Fe layer exist in the exchange-coupling films.…”
mentioning
confidence: 96%